Designer protein assemblies with tunable phase diagrams in living cells - Heidenreich, M; Georgeson, JM; Locatelli, E; Rovigatti, L; Nandi, SK; Steinberg, A; Nadav, Y; Shimoni, E; Safran, SA; Doye, JPK; Levy, ED (Nature Research, 2020)
Protein self-organization is a hallmark of biological systems. Although the physicochemical principles governing protein–protein interactions have long been known, the principles by which such nanoscale interactions generate diverse phenotypes of mesoscale assemblies, including phase-separated compartments, remain challenging to characterize. To illuminate such principles, we create a system of two proteins designed to interact and form mesh-like assemblies. We devise a new strategy to map high-resolution phase diagrams in living cells, which provide self-assembly signatures of this system. The structural modularity of the two protein components allows straightforward modification of their molecular properties, enabling us to characterize how interaction affinity impacts the phase diagram and material state of the assemblies in vivo. The phase diagrams and their dependence on interaction affinity were captured by theory and simulations, including out-of-equilibrium effects seen in growing cells. Finally, we find that cotranslational protein binding suffices to recruit a messenger RNA to the designed micron-scale structures.